Intra-familial and ethnic effects on attitudinal and perceptual body image: a cohort of South African mother-daughter dyads - Goedecke Julia H; Mchiza Zandile J; Lambert Estelle V (BMC, 2011)
Abstract Background International studies suggest ethnic differences in obesity prevalence may be due, in part, to differences in body image and body size dissatisfaction between groups. Further, there is evidence to suggest that there is a familial resemblance in body image between mothers and their younger (preadolescent) daughters. This research was therefore conducted to specifically identify the extent to which family status (presented as mother-daughter resemblance) and ethnicity impact on body image attitudes and perceptions of South African mothers and their pre-adolescent daughters. Methods Mother-daughter dyads (n = 201, 31% black, 37% mixed ancestry and 32% white) answered questions regarding their body image perception (the way they saw their body size status), their body image ideals, and body image attitudes (body size dissatisfaction in particular, presented as the Feel-Ideal Difference [FID] index score). Mothers' and daughters' body image results were compared within dyads and across ethnic groups using repeated measures of ANOVA. Results Overall, body image resemblances exist between South African mothers and their pre-adolescent daughters. Mothers and daughters chose similarly weighted silhouettes to represent their body size ideals (p = 0.308), regardless of their ethnicity or body mass index (BMI). The FID index scores were similar between mothers and their daughters only after the confounding effects of maternal BMI were removed (p = 0.685). The silhouettes chosen to represent thinness were also similar between mothers and their daughters (p = 0.960) regardless of ethnicity and maternal BMI. On the other hand, the silhouettes chosen to represent fatness were similar (p = 0.342) between mothers and their daughters, only after the confounding effects of maternal BMI were removed. Lastly, mothers and their daughters chose similarly weighted silhouettes as engendering feelings of beauty, respect and happiness (p = 0.813; p = 0.615 and p = 0.693, respectively). In this instance, black mother-daughter dyads chose significantly heavier silhouettes than the other ethnic groups. This implies that black mothers and daughters associate beauty, respect and happiness with a bigger body size. Conclusion Resemblances exist between pre-adolescent girls and their mothers on issues related to ideal and attitudinal body image. In this regard, South African researchers should consider the effects ethnicity and family status on body image of women when developing targeted interventions to prevent or manage obesity.